Reference values of spirometry parameters in healthy workers at different altitude levels in Peru - Llanos-Salcedo, Catherine (2020)
Objective: to estimate reference values for spirometry parameters in healthy workers at different altitude levels in Peru. Materials and methods: we performed a secondary analysis of records from occupational medical examinations carried out between May and June 2019 in workers at four different altitude levels: level 1: 0-100 m above sea level (ASL) (Trujillo, Pisco, Marcona, Lima), level 2: 2.300–2.800 m ASL (Arequipa and Cajamarca), level 3: 3.200–3.800 m ASL (Huancayo, La Oroya, Orcopampa, and Oyon); and level 4: 4.000–4.400 m ASL (Carhuacoto and Cerro de Pasco). Spirometry reference values for forced expiratory volume during the first second (FEV1), forced vital capacity (FVC), and the FEV1/FVC rate were constructed and compared using a multiple linear regression model. Results: we analyzed 33.232 records obtained from healthy workers in different altitude levels in Peru. In male subjects, FVC values were 4,6 ± 0,64 (mean ± standard deviation [SD]); 4,8 ± 0,67; 4,9 ± 0,65; and 4,8 ± 0,65 for altitude levels 1, 2, 3, and 4, respectively. Their corresponding lower limit of normal (LLN) values were 3,58; 3,78; 3,84; and 3,75 for altitude levels 1, 2, 3, and 4, respectively. FEV1 values were 3,8 ± 0,54; 3,9 ± 0,59; 4,0 ± 0,57; and 4,0 ± 0,59 for altitude levels 1, 2, 3, and 4, respectively. Their corresponding LLN values were 2,93; 3,06; 3,13; and 3,08 for levels 1, 2, 3, and 4, respectively. FEV/FVC rates were 0,83 ± 0,05; 0,83 ± 0,05; 0,84 ± 0,05; and 0,84 ± 0,05 for altitude levels 1, 2, 3, and 4, respectively. Their corresponding LLN values were 0,72; 0,71; 0,71; and 0,72 for altitude levels 1, 2, 3, and 4, respectively. Conclusions: both FEV1 and FVC spirometry values show mild differences according to altitude levels in the different evaluated areas. Further studies are necessary aiming to confirm our findings.